2017
DOI: 10.1002/bio.3281
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the intercalative binding modes of benzoyl peroxide with calf thymus DNA

Abstract: The binding of benzoyl peroxide (BPO), a flour brightener, with calf thymus DNA (ctDNA) was predicted by molecular simulation, and this were confirmed using multi-spectroscopic techniques and a chemometrics algorithm. The molecular docking result showed that BPO could insert into the base pairs of ctDNA, and the adenine bases were the preferential binding sites which were validated by the analysis of Fourier transform infrared spectra. The mode of binding of BPO with ctDNA was an intercalation as supported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The presence of isoelliptic points in the spectra suggests the presence of a single binding mechanism [ 21 ]. The red shift of the positive band (275 nm) may be the result of the conformational transition of ct DNA B-form to A-form through the weakening of the π-π* stacking of base pairs, an effect which may be the result of the insertion of the acridine ring into the DNA [ 22 ]. In comparison with the data obtained in the UV-Vis assays, it is possible to conclude that the results of the circular dichroism study support the hypothesis that binding occurred through intercalation in at least one part of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of isoelliptic points in the spectra suggests the presence of a single binding mechanism [ 21 ]. The red shift of the positive band (275 nm) may be the result of the conformational transition of ct DNA B-form to A-form through the weakening of the π-π* stacking of base pairs, an effect which may be the result of the insertion of the acridine ring into the DNA [ 22 ]. In comparison with the data obtained in the UV-Vis assays, it is possible to conclude that the results of the circular dichroism study support the hypothesis that binding occurred through intercalation in at least one part of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The variations of peak intensity in the CD spectra, in particular, indicated the stability of the right-handed B-form of ctDNA (Sharifinia et al, 2020 ), and the binding of NAA to ctDNA increased the base stacking degree of ctDNA and decreased the right-handed helicity of ctDNA (Li et al, 2014 ). Moreover, the red shift of the positive band demonstrated that ctDNA conformation tended to change from B-conformation to the more likely A-conformation as the π-π * stacking of base pairs was weakened when NAA was inserted into ctDNA (Xia et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%